Implementing Differentiated Instruction in Islamic Religious Education under the Merdeka Curriculum: A Comparative Case Study at Islamic and Public Junior Secondary Education - Churairoh Churairoh; Abdurrahmansyah Abdurrahmansyah; Tutut Handayani (AL-ISHLAH: Jurnal Pendidikan, 2025)
Differentiated instruction (DI) is a key component of Indonesia’s Merdeka Curriculum, aiming to address diverse student needs. However, its implementation in Islamic Religious Education (PAI) remains underexplored, particularly across different school contexts. This qualitative comparative case study examined how DI is implemented in PAI at two contrasting junior secondary schools: MTs Al-Azhar Center Baturaja (Islamic) and SMP Negeri 1 OKU (public). Fifteen Grade VIII PAI teachers were selected via purposive sampling. Data were collected through semi-structured interviews, classroom observations, and document analysis, then analyzed using the interactive model of Miles, Huberman, and Saldaña. Trustworthiness was ensured through triangulation and member checking. Findings show that both schools have initiated DI practices by mapping students’ learning styles and abilities, developing adaptive teaching modules, and applying varied strategies integrated with religious values. However, DI is often misinterpreted as grouping by learning styles alone, with limited application of content and product differentiation. Major challenges include partial conceptual understanding, low digital literacy, limited infrastructure, and inconsistency between planning and classroom execution. The study reveals that while teachers are beginning to adopt DI in PAI, implementation remains superficial and fragmented. Institutional support, teacher professional development, and clearer operational guidance are essential to deepen DI practices and align them with the goals of the Merdeka Curriculum.